Mullite amorphous material for garbage incinerator and production process of mullite amorphous material

By using ambly refractory materials prepared by lightweight porous mullite and other auxiliary materials, the problem of high thermal conductivity of refractory materials in waste incinerators is solved, and the effect of reducing heat loss and improving energy utilization is achieved.

CN119430958AActive Publication Date: 2025-02-14YIXING HAIKE REFRACTORY PROD CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411035684.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-07-31
Publication Date
2025-02-14
Estimated Expiration
2044-07-31

AI Technical Summary

Technical Problem

The existing amorphous refractory materials have a high thermal conductivity in waste incinerators, resulting in rapid heat loss and serious energy waste.

Method used

Lightweight porous mullite is used as aggregate, combined with calcium aluminate cement, alumina fine powder, silicon micro powder, kaolin and sodium hexametaphosphate and other auxiliary materials, and form an ambiguous material through a specific preparation process to reduce thermal conductivity and improve resistance. Corrosion performance.

Benefits of technology

It effectively reduces the thermal conductivity of the amorphous material, reduces heat loss, improves energy utilization, and improves corrosion resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004971007510000061
    Figure BDA0004971007510000061
  • Figure BDA0004971007510000071
    Figure BDA0004971007510000071
  • Figure BDA0004971007510000072
    Figure BDA0004971007510000072
Patent Text Reader

Abstract

The invention relates to the technical field of refractory materials, in particular to a mullite amorphous material for a garbage incinerator and a production process of the mullite amorphous material. The amorphous material comprises the following components in parts by weight: 60-75 parts of light porous mullite, 10-20 parts of calcium aluminate cement, 4-10 parts of aluminum oxide fine powder, 6-12 parts of silica powder, 1-3 parts of hydroxymethyl cellulose, 2-5 parts of kaolin and 0.5-1 part of sodium hexametaphosphate. The light porous mullite is adopted as the aggregate to be matched with other auxiliary materials to prepare the amorphous material, the cured amorphous material is excellent in corrosion resistance, uniform pores exist in the amorphous material, the heat conductivity coefficient of the amorphous material can be effectively reduced, heat loss is reduced, and the energy utilization rate is increased.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of refractory materials, in particular to a mullite unshaped material for a garbage incinerator and a production process thereof. Background Art

[0002] A waste incinerator is a device used to treat waste. It burns waste into ashes and smoke at high temperatures and quickly decomposes toxic substances to achieve harmless treatment. Therefore, waste incineration has become the main method for treating solid waste. The working temperature of a waste incinerator is 1200℃~1700℃, so a waste incinerator requires good refractory materials as its lining.

[0003] Refractory materials are divided into unshaped refractory materials and shaped refractory materials. Shaped refractory materials are usually refractory bricks, which have standard shapes and can be processed according to specific dimensions. However, when using shaped refractory materials, they must be processed according to the use environment, which is inconvenient to use and has a small scope of application. Unshaped refractory materials are mixed powder particles composed of multiple aggregates or aggregates and binders. They can be used directly or poured after adding appropriate liquids.

[0004] Existing amorphous refractory materials mostly use mullite as aggregate, but the thermal conductivity of mullite refractory is relatively high, and the heat in the waste incinerator will be lost quickly, resulting in a large waste of energy. Summary of the invention

[0005] In order to solve the above problems, the present invention provides a mullite unshaped material for a garbage incinerator and a production process thereof.

[0006] The technical solution of the present invention is: a mullite amorphous material for a garbage incinerator, which comprises the following components by weight: 60-75 parts of lightweight porous mullite, 10-20 parts of calcium aluminate cement, 4-10 parts of alumina fine powder, 6-12 parts of silicon micropowder, 1-3 parts of hydroxymethyl cellulose, 2-5 parts of kaolin, and 0.5-1 part of sodium hexametaphosphate.

[0007] Description: The above-mentioned lightweight porous mullite is used as aggregate and mixed with other auxiliary materials to form an amorphous material. The solidified amorphous material has excellent corrosion resistance, and there are uniform pores inside the amorphous material, which can effectively reduce the thermal conductivity of the amorphous material, reduce heat loss, and improve energy utilization.

[0008] Furthermore, the method for preparing the lightweight porous mullite comprises the following steps:

[0009] S1. Add aluminum nitrate and zinc nitrate into anhydrous ethanol, stir until dissolved, and obtain a mixed solution; the mass ratio of aluminum nitrate, zinc nitrate and anhydrous ethanol is 2-3:1-1.5:7-9;

[0010] S2. The pH value of the mixed solution is adjusted to 2-3 using dilute hydrochloric acid with a mass concentration of 15-20%, and then, under stirring, ethyl orthosilicate is continuously added to the mixed solution, and the amount of ethyl orthosilicate added per minute accounts for 2-3% of the initial mass of the mixed solution, until a precursor is obtained after 10-12 minutes, and a binder is added to the mixed solution once every 3-4 minutes during the addition of ethyl orthosilicate; the single addition amount of the binder accounts for 0.1-0.2% of the initial mass of the mixed solution;

[0011] S3, stirring the precursor at 60-70° C. for 0.5-1 h, and then standing for 1-1.5 h to obtain a mixed gel;

[0012] S4, drying the mixed gel, and then sintering the dried mixed gel at 1200-1300° C. for 2-3 hours to obtain lightweight porous mullite.

[0013] Description: In the above process, ethyl orthosilicate will hydrolyze to produce silicic acid, which will condense to form a three-dimensional silicon-oxygen network. At the same time, aluminum ions and zinc ions will react with silicic acid to form aluminum silicate and zinc silicate, and enter the silicon-oxygen network under the action of the binder to form a silicate mixed gel. Then, through sintering, a mullite structure will appear in the mixed gel, and the zinc silicate in the mixed gel will decompose at high temperature, so that uniform pores will appear in the mullite structure to reduce the thermal conductivity of the mullite. After the zinc silicate decomposes, a zinc oxide layer will be formed in the pores, which improves the corrosion resistance in the pores.

[0014] Furthermore, in step S2, the binder is a mixture of butyl acrylate and dioctyl phthalate in a ratio of 1:1.2 to 1.6.

[0015] Description: The above binder can effectively combine silicates to form a mixed gel, and zinc silicate can be evenly distributed in the mixed gel.

[0016] Furthermore, in step S2, the initial temperature of the mixed solution is 15-25°C, and after each addition of the binder, the temperature of the mixed solution is increased by 3-5°C.

[0017] Note: Gradually increasing the temperature of the mixed solution can allow the ethyl orthosilicate to fully react and form a mixed gel under the action of the binder, thereby improving the conversion rate of the mixed gel.

[0018] Furthermore, in step S4, the drying temperature is 130-150° C., and the drying time is 30-40 minutes.

[0019] Note: The above drying parameters can ensure that the water in the mixed gel is fully removed to form a dry gel.

[0020] Furthermore, in step S4, the temperature rise curve during sintering is: heating to 280-320°C at a heating rate of 3-5°C / min, and keeping warm for 15-20min; then heating to 760-800°C at a heating rate of 6-8°C / min, and keeping warm for 30-40min; then heating to 1000-1100°C at a heating rate of 10-12°C / min, and keeping warm for 50-60min; then heating to 1200-1300°C at a heating rate of 6-8°C / min.

[0021] Note: The above heating curve can form a stable mullite structure, ensure that the mullite grains are small and uniform, and ensure that zinc silicate can be fully decomposed to form uniform pores inside the mullite.

[0022] Furthermore, the average particle size of the alumina fine powder is 1.0 μm to 3.0 μm.

[0023] Note: Alumina powder with the above particle size can adjust the fluidity and wear resistance of amorphous materials.

[0024] Furthermore, the average particle size of the silicon powder is ≤1.0 μm.

[0025] Note: Silicon powder with the above particle size can improve the mechanical strength and structural uniformity of amorphous materials.

[0026] On the other hand, the present invention provides a production process of mullite amorphous material for a waste incinerator, which is used to prepare the above-mentioned mullite amorphous material for a waste incinerator, comprising the following steps:

[0027] Step 1: Put lightweight porous mullite, calcium aluminate cement, alumina fine powder, silica powder and kaolin into a mixer, and stir for 10 to 15 minutes to obtain a mixture;

[0028] Step 2: Add 10-15% of water to the mixture, then add sodium hexametaphosphate and hydroxymethyl cellulose to the mixture, and continue stirring for 20-30 minutes to obtain a mullite amorphous material.

[0029] Description: The mullite amorphous material prepared by the above process has uniform internal composition, fine grains after solidification, high internal porosity, low thermal conductivity, and excellent corrosion resistance.

[0030] The beneficial effects of the present invention are:

[0031] (1) The present invention uses lightweight porous mullite as an aggregate and combines it with other auxiliary materials to form an amorphous material. The solidified amorphous material has excellent corrosion resistance and uniform pores inside the amorphous material, which can effectively reduce the thermal conductivity of the amorphous material, reduce heat loss, and improve energy utilization.

[0032] (2) In the present invention, ethyl orthosilicate will hydrolyze to produce silicate, which will condense to form a three-dimensional silicon-oxygen network. At the same time, aluminum ions and zinc ions will react with silicate to generate aluminum silicate and zinc silicate, and form a silicate mixed gel under the action of a binder. Then, a mullite structure will appear in the mixed gel through sintering, and the zinc silicate in the mixed gel will decompose at high temperature, so that uniform pores will appear in the mullite structure to reduce the thermal conductivity of the mullite. After the zinc silicate is decomposed, a zinc oxide layer will be formed in the pores, thereby improving the corrosion resistance in the pores.

[0033] (3) The mullite amorphous material prepared by the process of the present invention has uniform internal composition, fine grains after solidification, high internal porosity, low thermal conductivity, and excellent corrosion resistance. DETAILED DESCRIPTION

[0034] In order to further illustrate the method and effect of the present invention, the technical solution of the present invention will be clearly and completely described in combination with experiments.

[0035] Example 1: A mullite amorphous material for a waste incinerator, comprising the following components by weight: 68 parts of lightweight porous mullite, 15 parts of calcium aluminate cement, 7 parts of alumina fine powder, 8 parts of silicon powder, 2 parts of hydroxymethyl cellulose, 3 parts of kaolin, and 0.75 parts of sodium hexametaphosphate;

[0036] The preparation method of lightweight porous mullite comprises the following steps:

[0037] S1. Add aluminum nitrate and zinc nitrate into anhydrous ethanol and stir until dissolved to obtain a mixed solution; the mass ratio of aluminum nitrate, zinc nitrate and anhydrous ethanol is 2.5:1.25:8;

[0038] S2. The pH value of the mixed solution is adjusted to 2.5 using dilute hydrochloric acid with a mass concentration of 18%, and then, under stirring, tetraethyl orthosilicate is continuously added to the mixed solution, and the amount of tetraethyl orthosilicate added per minute accounts for 2.5% of the initial mass of the mixed solution, until a precursor is obtained after 11 minutes, and a binder is added to the mixed solution once every 3.5 minutes during the addition of tetraethyl orthosilicate; the single addition amount of the binder accounts for 0.15% of the initial mass of the mixed solution;

[0039] The binder is a mixture of butyl acrylate and dioctyl phthalate in a ratio of 1:1.4;

[0040] The initial temperature of the mixed solution was 20°C, and after each addition of the binder, the temperature of the mixed solution was increased by 4°C;

[0041] S3, stirring the precursor at 65°C for 0.75h, and then standing for 1.25h to obtain a mixed gel;

[0042] S4, drying the mixed gel, and then sintering the dried mixed gel at 1250° C. for 2.5 h to obtain lightweight porous mullite; the drying temperature is 140° C., and the drying time is 35 min;

[0043] The heating curve during sintering is as follows: heating to 300°C at a heating rate of 4°C / min, keeping warm for 18 minutes; then heating to 780°C at a heating rate of 7°C / min, keeping warm for 35 minutes; then heating to 1050°C at a heating rate of 11°C / min, keeping warm for 55 minutes; then heating to 1250°C at a heating rate of 7°C / min;

[0044] The average particle size of alumina fine powder is 1.0μm to 3.0μm, and the average particle size of silicon powder is ≤1.0μm;

[0045] The production process of the above-mentioned mullite unshaped material for garbage incinerator comprises the following steps:

[0046] Step 1: Put lightweight porous mullite, calcium aluminate cement, alumina fine powder, silica powder and kaolin into a mixer and stir for 13 minutes to obtain a mixture;

[0047] Step 2: Add 12% water to the mixture, then add sodium hexametaphosphate and hydroxymethyl cellulose to the mixture, and continue stirring for 25 minutes to obtain a mullite amorphous material.

[0048] Example 2: This example is basically the same as Example 1, except that the mullite amorphous material for a waste incinerator includes the following components by weight: 60 parts of lightweight porous mullite, 10 parts of calcium aluminate cement, 4 parts of alumina fine powder, 6 parts of silicon micropowder, 1 part of hydroxymethyl cellulose, 2 parts of kaolin, and 0.5 parts of sodium hexametaphosphate.

[0049] Example 3: This example is basically the same as Example 1, except that the mullite amorphous material for a waste incinerator includes the following components by weight: 75 parts of lightweight porous mullite, 20 parts of calcium aluminate cement, 10 parts of alumina fine powder, 12 parts of silicon micropowder, 3 parts of hydroxymethyl cellulose, 5 parts of kaolin, and 1 part of sodium hexametaphosphate.

[0050] Example 4: This example is basically the same as Example 1, except that the mass ratio of aluminum nitrate, zinc nitrate and anhydrous ethanol is 2:1:7.

[0051] Example 5: This example is basically the same as Example 1, except that the mass ratio of aluminum nitrate, zinc nitrate and anhydrous ethanol is 3:1.5:9.

[0052] Example 6: This example is basically the same as Example 1, except that the pH value of the mixed solution is adjusted to 2 using dilute hydrochloric acid with a mass concentration of 18%.

[0053] Example 7: This example is basically the same as Example 1, except that the pH value of the mixed solution is adjusted to 3 using dilute hydrochloric acid with a mass concentration of 18%.

[0054] Example 8: This example is basically the same as Example 1, except that the amount of tetraethyl orthosilicate added per minute accounts for 2% of the initial mass of the mixed solution.

[0055] Example 9: This example is basically the same as Example 1, except that the amount of tetraethyl orthosilicate added per minute accounts for 3% of the initial mass of the mixed solution.

[0056] Example 10: This example is basically the same as Example 1, except that the single addition amount of the binder accounts for 0.1% of the initial mass of the mixed solution.

[0057] Example 11: This example is basically the same as Example 1, except that the single addition amount of the binder accounts for 0.2% of the initial mass of the mixed solution.

[0058] Example 12: This example is basically the same as Example 1, except that the binder is a mixture of butyl acrylate and dioctyl phthalate in a ratio of 1:1.2.

[0059] Example 13: This example is basically the same as Example 1, except that the binder is a mixture of butyl acrylate and dioctyl phthalate in a ratio of 1:1.6.

[0060] Example 14: This example is basically the same as Example 1, except that after each addition of the binder, the mixed solution is raised by 3°C.

[0061] Example 15: This example is basically the same as Example 1, except that after each addition of the binder, the mixed solution is raised by 5°C.

[0062] Example 16: This example is basically the same as Example 1, except that the temperature rise curve during sintering is as follows: heat to 280°C at a heating rate of 3°C / min, and keep warm for 15 minutes; heat to 760°C at a heating rate of 6°C / min, and keep warm for 30 minutes; heat to 1000°C at a heating rate of 10°C / min, and keep warm for 50 minutes; heat to 1200°C at a heating rate of 6°C / min.

[0063] Example 17: This example is basically the same as Example 1, except that the temperature rise curve during sintering is as follows: heat to 320°C at a heating rate of 5°C / min, and keep warm for 20 minutes; heat to 800°C at a heating rate of 8°C / min, and keep warm for 40 minutes; heat to 1100°C at a heating rate of 12°C / min, and keep warm for 60 minutes; heat to 1300°C at a heating rate of 8°C / min.

[0064] Example 18: This example is basically the same as Example 1, except that the mixed gel is sintered at 1200°C for 2 hours.

[0065] Example 19: This example is basically the same as Example 1, except that the mixed gel is sintered at 1300°C for 3 hours.

[0066] Comparative Example 1: Commercially available mullite particles were used to replace the lightweight porous mullite.

[0067] Comparative Example 2: Both the tetraethyl orthosilicate and the binder were added all at once.

[0068] Comparative Example 3: The temperature of the mixed solution was kept constant at 20°C without any change.

[0069] Comparative Example 4: During sintering, the temperature was raised to 1250° C. at a heating rate of 11° C. / min.

[0070] Experimental example: In order to explore the influence of the parameters of each embodiment on the performance of the amorphous material, the amorphous material prepared in each embodiment is placed in a mold, and after vibration, it is baked at 120°C for 28 hours, and the sample is demolded to obtain the thermal conductivity of the sample of each embodiment, and the thermal conductivity at 1200°C is obtained. The sample of each embodiment is immersed in a 10% sodium hydroxide solution for 24 hours to obtain the mass loss rate of the sample of each embodiment, which is as follows:

[0071] Experimental Example 1: Investigating the influence of ingredients on the performance of amorphous materials

[0072] Using Examples 1 to 3 and Comparative Example 1 as experimental comparison, the properties of the amorphous materials under different compositions are shown in Table 1 below:

[0073] Table 1 Performance of amorphous materials with different compositions

[0074] Group Thermal conductivity W / (m·k) Quality loss rate Example 1 0.62 0.19% Example 2 0.70 0.23% Example 3 0.68 0.22% Comparative Example 1 1.53 0.55%

[0075] It can be seen from the data in Table 1 that compared with Examples 1, 2, and 3, the composition of the amorphous material will affect the performance of the amorphous material. Among them, the sample of Example 1 has the lowest thermal conductivity and the smallest mass loss rate, indicating that the sample of Example 1 has the best thermal insulation performance and corrosion resistance. This may be because the internal pores of the sample of Example 1 are uniform and have fewer defects. Therefore, the composition of the amorphous material selected in Example 1 is optimal;

[0076] Compared with Comparative Example 1, after the commercially available mullite particles were used to replace the lightweight porous mullite, the thermal insulation performance and corrosion resistance of the sample decreased. This may be because after the lightweight porous mullite was used, uniform pores existed inside the amorphous material, and a zinc oxide coating existed in the pores, which reduced the corrosion in the pores.

[0077] Experimental Example 2: Investigating the effects of mixed solution ratio and pH value on the properties of amorphous materials

[0078] Using Example 1 and Examples 4 to 7 as experimental comparisons, the properties of the amorphous material at different proportions of the mixed solution and different pH values ​​are shown in Table 2 below:

[0079] Table 2 Performance of amorphous materials at different proportions and pH values ​​of mixed solutions

[0080]

[0081]

[0082] It can be seen from the data in Table 2 that compared with Examples 1, 4, 5, 6, and 7, too high or too low mixed solution ratios and pH values ​​will lead to reduced performance of the amorphous material, among which the sample in Example 1 has the lowest thermal conductivity and the smallest mass loss rate, so the mixed solution ratio and pH value selected in Example 1 are both optimal;

[0083] Experimental Example 3: Investigating the effect of the amount of ethyl orthosilicate added on the performance of amorphous materials

[0084] Using Example 1, Examples 8 to 9, and Comparative Example 2 as experimental comparisons, the properties of the amorphous material obtained under different addition amounts of tetraethyl orthosilicate are shown in Table 3 below:

[0085] Table 3 Performance of amorphous materials with different addition amounts of ethyl orthosilicate

[0086] Group Thermal conductivity W / (m·k) Quality loss rate Example 1 0.62 0.19% Example 8 0.76 0.28% Example 9 0.72 0.25% Comparative Example 2 1.21 0.44%

[0087] It can be seen from the data in Table 3 that compared with Examples 1, 8, and 9, too high or too low an amount of tetraethyl orthosilicate added will lead to reduced performance of the amorphous material, among which the sample in Example 1 has the lowest thermal conductivity and the smallest mass loss rate, so the amount of tetraethyl orthosilicate added selected in Example 1 is optimal;

[0088] Compared with Comparative Example 2, in Example 1, after the one-time addition of tetraethyl orthosilicate, the thermal conductivity and mass loss rate of the sample both increased. This may be because after the one-time addition of tetraethyl orthosilicate, the zinc ions cannot be evenly distributed in the mixed gel, resulting in uneven pores in the mullite.

[0089] Experimental Example 4: Investigating the effect of the amount and composition of binder on the performance of amorphous materials

[0090] Using Example 1 and Examples 10 to 13 as experimental comparisons, the properties of the amorphous material with different addition amounts of the binder and different components are shown in Table 4 below:

[0091] Table 4 Performance of amorphous materials with different addition amounts of binder and different compositions

[0092]

[0093]

[0094] It can be seen from the data in Table 4 that compared with Examples 1, 10, 11, 12, and 13, the amount and composition of the binder added will affect the performance of the amorphous material, among which the sample of Example 1 has the lowest thermal conductivity and the smallest mass loss rate. Therefore, the amount and composition of the binder selected in Example 1 are optimal.

[0095] Experimental Example 5: Investigating the effect of mixed solution temperature on the performance of amorphous materials

[0096] Using Example 1, Examples 14-15, and Comparative Example 3 as experimental comparisons, the properties of the amorphous material obtained at different temperatures of the mixed solution are shown in Table 5 below:

[0097] Table 5 Performance of amorphous materials at different temperatures of mixed solution

[0098] Group Thermal conductivity W / (m·k) Quality loss rate Example 1 0.62 0.19% Embodiment 14 0.77 0.28% Embodiment 15 0.74 0.25% Comparative Example 3 0.93 0.35%

[0099] It can be seen from the data in Table 5 that compared with Examples 1, 14, and 15, the temperature of the mixed solution being too high or too low will affect the performance of the amorphous material. Among them, the thermal conductivity of the sample in Example 1 is the lowest and the mass loss rate is the smallest. Therefore, the temperature of the mixed solution selected in Example 1 is the best;

[0100] Compared with Comparative Example 3, when the temperature of the mixed solution does not change, the thermal conductivity and mass loss rate of the sample in Example 1 both increase. This may be because when the temperature of the mixed solution does not change, the conversion rate of the mixed gel is low and the pores inside the mullite are uneven.

[0101] Experimental Example 6: Investigating the influence of sintering parameters on the performance of amorphous materials

[0102] Using Example 1, Examples 16 to 19 and Comparative Example 4 as experimental comparisons, the properties of the amorphous material under different sintering parameters are shown in Table 6 below:

[0103] Table 6 Properties of amorphous materials under different sintering parameters

[0104]

[0105]

[0106] It can be seen from the data in Table 6 that compared with Examples 1, 16, 17, 18, and 19, the temperature rise curve and sintering parameters during sintering will affect the performance of the amorphous material. Among them, the sample of Example 1 has the lowest thermal conductivity and the smallest mass loss rate. Therefore, the sintering parameters selected in Example 1 are optimal.

[0107] Compared with Comparative Example 4, in Example 1, after the heating rate during sintering was constant, the thermal conductivity and mass loss rate of the sample both increased. This may be because the heating rate during sintering was constant, which resulted in the inability to fully decompose zinc silicate and form pores inside the mullite.

Claims

1. A mullite unshaped material for a waste incinerator, characterized in that: The composition includes the following components by weight: 60-75 parts of lightweight porous mullite, 10-20 parts of calcium aluminate cement, 4-10 parts of alumina fine powder, 6-12 parts of silicon micropowder, 1-3 parts of hydroxymethyl cellulose, 2-5 parts of kaolin and 0.5-1 part of sodium hexametaphosphate.

2. The mullite unshaped material for a waste incinerator according to claim 1, characterized in that: The preparation method of the lightweight porous mullite comprises the following steps: S1. Add aluminum nitrate and zinc nitrate into anhydrous ethanol, stir until dissolved, and obtain a mixed solution; the mass ratio of aluminum nitrate, zinc nitrate and anhydrous ethanol is 2-3:1-1.5:7-9; S2. The pH value of the mixed solution is adjusted to 2-3 using dilute hydrochloric acid with a mass concentration of 15-20%, and then, under stirring, ethyl orthosilicate is continuously added to the mixed solution, and the amount of ethyl orthosilicate added per minute accounts for 2-3% of the initial mass of the mixed solution, until a precursor is obtained after 10-12 minutes, and a binder is added to the mixed solution once every 3-4 minutes during the addition of ethyl orthosilicate; the single addition amount of the binder accounts for 0.1-0.2% of the initial mass of the mixed solution; S3, stirring the precursor at 60-70° C. for 0.5-1 h, and then standing for 1-1.5 h to obtain a mixed gel; S4, drying the mixed gel, and then sintering the dried mixed gel at 1200-1300° C. for 2-3 hours to obtain lightweight porous mullite.

3. The mullite unshaped material for a waste incinerator according to claim 2, characterized in that: In step S2, the binder is a mixture of butyl acrylate and dioctyl phthalate in a ratio of 1:1.2 to 1.

6.

4. The mullite unshaped material for a waste incinerator according to claim 2, characterized in that: In step S2, the initial temperature of the mixed solution is 15-25°C, and after each addition of the binder, the temperature of the mixed solution is increased by 3-5°C.

5. The mullite unshaped material for a waste incinerator according to claim 2, characterized in that: In step S4, the drying temperature is 130-150° C., and the drying time is 30-40 minutes.

6. The mullite unshaped material for a waste incinerator according to claim 2, characterized in that: In step S4, the temperature rise curve during sintering is: heating to 280-320°C at a heating rate of 3-5°C / min, and keeping warm for 15-20min; then heating to 760-800°C at a heating rate of 6-8°C / min, and keeping warm for 30-40min; then heating to 1000-1100°C at a heating rate of 10-12°C / min, and keeping warm for 50-60min; then heating to 1200-1300°C at a heating rate of 6-8°C / min.

7. The mullite unshaped material for a waste incinerator according to claim 1, characterized in that: The average particle size of the alumina fine powder is 1.0 μm to 3.0 μm.

8. The mullite unshaped material for a waste incinerator according to claim 1, characterized in that: The average particle size of the silicon powder is ≤1.0 μm.

9. A production process of mullite unshaped material for waste incinerator, used for producing the mullite unshaped material for waste incinerator as claimed in any one of claims 1 to 8, characterized in that: The following steps are involved: Step 1: Put lightweight porous mullite, calcium aluminate cement, alumina fine powder, silica powder and kaolin into a mixer, and stir for 10 to 15 minutes to obtain a mixture; Step 2: Add 10-15% of water to the mixture, then add sodium hexametaphosphate and hydroxymethyl cellulose to the mixture, and continue stirring for 20-30 minutes to obtain a mullite amorphous material.

Citation Information

Patent Citations

  • Light-weight mullite refractory material and preparation method thereof

    CN107266097A

  • Light-weight corundum-mullite castable and preparation method thereof

    CN107311680A

  • MOFs particle doped composite material and preparation method thereof

    CN114213754A

  • PCBN composite material and preparation method thereof

    CN114276151A

  • Zirconium mullite composite silicon carbide castable for garbage incinerator and prefabricated part

    CN115819097A